STRATEGI PENGEMBANGAN SDM DALAM MENDUKUNG KEBIJAKAN MBKM DI FAKULTAS TEKNOLOGI PANGAN DAN KESEHATAN - Rahmawati, Rahmawati; Pujilestari, Shanti; Hamidatun, Hamidatun (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Independent Learning Independent Campus (MBKM) was initiated by The Ministry Education and Culture in 2020 is one of the policy in order to prepare a great generation in againts of the industrial revolution 4.0. The success of MBKM program requires a synergistic role from all elements of human resources in university including lecturer and education staff.  Faculty of Food Technology  and Health, Sahid University, Jakarta has implemented MBKM program since 2021 with 2 main programs namely entrepreneurship and humanitarian projects. The aims of this study were to analyze the strengths and weaknesses of lecturers and education staff and prepare startegies to develop the quality of  lecturers and education staff in supporting MBKM policies. The result show that there will be further sozialization about MBKM policy for lecturers and education staff. The faculty also encourage lecturers to meet the qualifications and competencies as supervisors of MBKM program. Educational staff will be strengthen in the function as administration, management, supervision and technical services regarding MBKM activities